Diseño e implementación de un sistema de paneles solares fotovoltaicos con capacidad de 35 Kw.h/mes para transmitir la energía eléctrica generada al compresor de una bomba de calor. - Almeida Vásquez, Edgar Gabriel (2018)
The present project consists of designing and implementing a photovoltaic solar system consisting of four photovoltaic solar panels, a voltage controller, an inverter of 1500 W, a bank of 4 deep discharge batteries of 13,3 V , to generate 1000 Was maximum capacity in any climatic condition that is. For the verification of the operation of the system, a heat pump was connected, with a 1 HP compressor. The results obtained from the tests performed on the heat pump were tabulated with experimental data taken every 2 minutes, these tests had an approximate time of 20 minutes for each heating process. The maximum temperature reached in the condenser by water was 50 ° C, a quality of 35,32 %, the transfer of heat reached in high and low was 182,20-151,47 (kJ/kg) respectively, there was also a network consumed of 30,73 (kJ/kg) and a performance coefficient of 5,93. It also connected several devices at the same time to the solar photovoltaic system to verify that they can work without any problem. The implementation of the solar photovoltaic system has a slightly high initial cost, which can be recovered, in a long term; However, the photovoltaic solar system has a useful life of 25 years or more, depending on the maintenance applied to it, this design and implementation, helps with the environment by not using fossil fuels to generate electric power, in addition the system can stop to emit 66,4 kg of per year. As a complement to this research, a meteorological station was used, which gave different climatic parameters, such as ambient temperature, wind speed and incident radiation.